INTERDISCIPLINARIDADE EM ESTRATÉGIA DE SAÚDE DA FAMÍLIA (ESF): ESTUDO NA CIDADE-SEDE DA 4ª REGIONAL DE SAÚDE DO PARANÁ - Schmitt, Vania (2015)
The main objective of this study was to diagnose and promote knowledge about interdisciplinary teams in the Family Health Strategy (FHS) for the host city of theth4 Regional Paraná State Health, the city of Irati. It was performed a bibliometric research in National Register of Health Establishments (NRHE), in order to obtain the information about the number of units with FHS teams in the city. After this step, a questionnaire was applied validated to diagnose the interdisciplinarity in the units. An interdisciplinary educational action was carried out by means of the methodology of the wheel of conversation and a album show, which aimed to increase knowledge of conceptual information about interdisciplinary work. To verify the results obtained with this educational activity, a questionnaire was applied validated to analyze the satisfaction of participants in relation to the intervention. For statistical analysis we used the chi-square and Fisher exact test, apart from logistic regression to assess the Association of variables and understanding of interdisciplinary work in teams. Forty-one individuals participated in the research of a total population of 44 professionals registered in the NRHE. It was observed that although the majority (87.8%) of professionals assert the existence of interdisciplinary work, there was no statistical difference between the evaluated variables. However, in relation to prior knowledge on the topic discussed in educational activity, it was found that the top-level professionals have greater understanding about the subject that the middle-level technical (p=0.012). The educational action presented positive evaluation by participants, however, stressed that the information received would have median contribution in their professional activity, due to some difficulties pointed out: lack of professional skills in interdisciplinary work teams. It is concluded that, overall, the professionals evaluated report having knowledge about the interdisciplinary work, in addition to claiming this practice despite the difficulties reported. It is suggested that new governmental actions are carried out in order to extend the teams and promote health education initiatives.